2007
DOI: 10.1017/s0265021506001529
|View full text |Cite
|
Sign up to set email alerts
|

Effect of vital capacity manoeuvres on arterial oxygenation in morbidly obese patients undergoing open bariatric surgery

Abstract: The addition of VCM to PEEP improves intraoperative arterial oxygenation in morbidly obese patients undergoing open bariatric surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
45
2
6

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(54 citation statements)
references
References 34 publications
1
45
2
6
Order By: Relevance
“…From five of those (182 patients), outcome data could be extracted and combined. 14 There were not enough data on other outcomes to draw any meaningful conclusions.…”
Section: Peep Alone Vs Peep Plus Recruitment Manoeuvrementioning
confidence: 99%
“…From five of those (182 patients), outcome data could be extracted and combined. 14 There were not enough data on other outcomes to draw any meaningful conclusions.…”
Section: Peep Alone Vs Peep Plus Recruitment Manoeuvrementioning
confidence: 99%
“…Common sense would suggest the application of PEEP, and the addition of periodic recruitment maneuvers (repeated sustained lung inflation with peak pressures of 40 cm H 2 O have been used) or vital capacity maneuvers has been shown to improve oxygenation beyond the application of PEEP alone. 96,97 These maneuvers should be followed by the application of PEEP to maintain recruitment. Positive end-expiratory pressure values of 10 cm H 2 O applied after recruitment/vital capacity maneuvers produce a lower A-a gradient than the application of zero PEEP (known as ZEEP) or 5 cm H 2 O PEEP in obese patients undergoing laparoscopic surgery.…”
Section: Oxygenation and Ventilationmentioning
confidence: 99%
“…This indicates better oxygenation levels with the use of NIV, probably due to an increase in functional residual capacity (FRC). Several ventilation strategies have been assessed for their effect on improving arterial oxygenation during the intraoperative period in patients with morbid obesity 21 . The use of CPAP restores the FRC to preoperative levels, improving PO oxygenation 3 .…”
Section: Discussionmentioning
confidence: 99%
“…The authors concluded that PEEP levels of around 15 cmH 2 O were necessary to prevent lung collapse and to improve gas exchange in morbidly obese patients. Chalhoub et al 21 assessed the effects of the vital capacity maneuver (VCM) in morbidly obese subjects submitted to open bariatric surgery and found that PEEP levels of 8 cmH 2 O associated to VCM were sufficient to significantly improve arterial oxygenation and to avoid hemodynamic instability. The levels of IPAP and EPAP used in the present study were based on these previous findings.…”
Section: Discussionmentioning
confidence: 99%